Development of Scoring System for Archery Competition Results Website Based - Afandi, Mahsus; Hartono, Mugiyo; Hanani, Endang Sri (Journal of Physical Education and Sports, 2021)
The purposes of the research are to develop a website-based archery competition scoring system and analyze the effectiveness of a website-based archery competition scoring system. This research is research development or Research and Development (R & D). The research method used is a research and development (R & D) scoring system for web-based archery competition results. The types of data in this research are quantitative data and qualitative data, quantitative data in the form of evaluation results of archery experts, technology experts and users of scoring systems, qualitative data in the form of observations. The data analysis technique used is descriptive analysis in the form of percentages. The results of this study are the product of a website-based archery competition scoring system product and a scorer application to enter scores into an android-based scoring system. The results of data analysis on the average score of expert assessment in trial 1 (one) was 74.6% and the results of data analysis on average score of expert assessment in trial 2 (two) was 88.2%. The results of data analysis from users of the scoring system related to the effectiveness of using the product of the scoring system were 87.2%. Conclusion, this research produces a website-based archery competition scoring system that is more effective in processing and presenting the results of archery competition scores.